Benefits of Employee Training at Putri Eceng Gallery, Klari District - Meri Antika; Adhe Oktapiani Sopian; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Formosa Journal of Science and Technology, 2023)
The handicraft business has bright prospects because handicraft products have an important role in supporting economic development in Indonesia. The existence of a handicraft activity program is one of the solutions to reduce vibrations in the countryside, increase people's income, increase the quality of human resources, and can create new jobs by maximizing the capabilities found in the rural environment. Galeri Putri Eceng is a home-based business in the Klari sub-district and is engaged in handicrafts. Galeri Putri Eceng is a business that makes products such as bags, tissue containers, chairs, tables, delivery containers (Javanese: peningset) for engagements or weddings, as well as various souvenirs made from water hyacinth. The purpose of observing this industrial visit is to find out the benefits of employee training at the Putri Waterceng Gallery. The method used in the results of this visit is a descriptive observation method. The subject of this concern is the employee at Galeri Putri Eceng. The benefit of employee training is to obtain customer satisfaction and product quality. This shows that job training is very important for workers so that they can better master the work they are carrying out and as an effort to prepare workers to face work tasks that are considered not yet mastered and as an effort to improve employee performance.